Kidung Jaka Bandung - TATANG RUSMANA (Institut Seni Indonesia Yogyakarta, 2008)
The Creation of Jaka Bandung Play. Jaka Bandung Play is created from a legend using Malabar Kingdom andBandung Lake as its story backgrounds. The name of the kingdom has been changed into Datarluhur Pangulinganfor the sake of the play. The story depicts the human existence of Parahyangan represented by Rahiang JakaBandung. The play is approached by using particular technique of directing, so called “verbal arts”. Its presentationon stage relies on beauty, hyper reality, theatricality and new theater codes.